Methodological design support for new-generation airship gas-air system - Alexander Nikolayevich Kirilin; Anna Alexandrovna Boldyreva (Advanced Engineering Research)
The research subject is a design process of gas-air system (GAS) of multi-purpose, transport, and high-altitude (including stratospheric) airships. This research objectives are a methodological design support of the new-generation airship GAS; the development of practical recommendations for selecting geometrical and physical parameters of the basic GAS elements. The functionality of the new-type airship GAS is analyzed. The design technique of the multi-purpose, transport, and high-altitude (including stratospheric) airship basic GAS parameters as applied to the adiabatic process of heat exchange of the buoyant gas and air in the airframe with the environment is developed. The algorithm corresponding to the offered technique has been implemented and introduced in the «Aerostatics» block of the updated conceptual software for various types of airships. The algorithm is written in the object-oriented C++ programming. The basic airship GAS parameters depending on their volume, flight altitude, climbing rate, and gas type (air, helium, phlegmatized hydrogen) are studied. The presented table and graphic interpretations of the GAS calculated parameters of the airships of different purpose in a wide range of their dimensions allow develop some practical recommendations for selecting the geometrical and physical parameters of the basic GAS elements. These findings can be used by the aircraft community in developing advanced models of the aeronautic equipment.